Biosorption of copper from synthetic waters by using tobacco leaf: equilibrium, kinetic and thermodynamic tests - Çekim, Mehmet; Yildiz, Sayiter; Dere, Turgay (Journal of Environmental Engineering and Landscape Management, 2015)
Abstract. In this study, biosorption of Cu2+ ions on to tobacco leaves was investigated. The optimum conditions for biosorption of Cu2+ ions onto tobacco leaves were determined: pH – 4.0, temperature – 20 °C, shaking rate – 200 rpm, biosorbent dose – 0.4 g, and initial Cu2+ ion concentration – 25 mg/L. The state of equilibrium lasted for 60 minutes. COD, TN and TP analyses were performed to determine the negative impacts of biosorbent on the system. Compliance of equilibrium data of tobacco biosorption of Cu2+ ions to Langmuir, Freundlich, Temkin and D–R isotherm models was also investigated. High correlations were achieved in all four isotherm models. Within the scope of kinetic tests, it was observed that biosorption of Cu2+ ions with tobacco biosorbent complied with the pseudo second-order kinetic rate constant. FTIR, SEM and EDX analyses were carried out to investigate the surface characteristics and chemical structure of tobacco biosorbent and absorption of Cu2+ ions were observed. It was concluded that tobacco leaves are a highly efficient (90.72%) sorbent that can remove Cu2+ ions from wastewater.